Identification of genes differentially expressed in onion infected with Iris yellow spot virus - ABDELKHALEK, Ahmed; ELMORSI, Adel; ALSHEHABY, Omar; SANAN-MISHRA, Neeti; HAFEZ, Elsayed (Phytopathologia Mediterranea, 2018)
Iris yellow spot virus (IYSV) causes severe damage and economic losses in onion production. Differential display-PCR was used to study changes in the gene expression of IYSV-infected onion plants. Representative up-regulated and down-regulated genes were selected for further study. Based on sequence analysis, the up-regulated genes were identified as retrotransposon protein, disease resistance-like proteins, chitinase, pathogenesis-related protein, cytochrome oxidase, cytochrome c, pentatricopeptide repeat-containing protein and pectin methylesterase. A DNA-binding transcriptional repressor protein gene was greatly down-regulated. . Most of the identified genes are known to play essential roles in plant defence systems, and are newly identified in onion sequences.